(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article weaves a critique of modern separability, drawing from Karen Barad and Denise Ferreira da Silva. It proposes a relational aesthetic-politics, understanding the phenomena between matters as a fundamental dimension – the invitation is to unleash the creative capacity of imagination beyond separation. This debate materializes itself in Emaranhada, a project that involved artists, waste pickers, biologists, educators, fishers and crab gatherers. Examining the relational aesthetics proposed by Nicolas Bourriaud, and its critique made by Claire Bishop, the article also shares recent interinstitutional actions by Eleonora Fabião to consider, along with André Lepecki, a poetics of proliferation.